Elastography and contrast‐enhanced ultrasound to assess the effect of varicocelectomy: A case‐controlled study. (10th October 2022) - Cao, Wen; Han, Hu; Guan, Xing; Lyu, Chaoyang; Zhou, Qian; Tian, Long; Guo, Ruijun
Abstract: To evaluate the changes in testicular stiffness and microcirculation caused by spermatic vein ligation in patients with varicocele, we conducted a case‐controlled study. A total of 27 grade III left varicocele cases were enrolled. Testicular stiffness and perfusion were evaluated by shear wave elastography and contrast‐enhanced ultrasound during subinguinal microscopic varicocelectomy. The external and the internal parenchyma of bilateral testes were selected to compare the shear wave velocity of bilateral testes during the spermatic vein ligation. We mapped and compared the intensity‐time curves following bolus contrast injection three times in the same region of interest. Initially, the shear wave velocity of the left internal parenchyma was higher than the right side (1.10 ± 0.06 m/s vs. 1.00 ± 0.03 m/s). It decreased (1.09 ± 0.06 m/s) ( p < 0.05) after ligation. Meanwhile, the left epididymis had the higher agent peak intensity (0.90 × 10E−5 AU), the largest area under the curve (80.20 × 10E−5 AU s), and the longest washout area (54.35 × 10E−5 AU s). In addition, the left internal parenchyma presented a sharper slope (0.18 × 10E−5 AU/s) ( p < 0.05). In conclusion, the spermatic vein ligation improved the perfusion of the internal testicular parenchyma, but it could temporally deteriorate the stasis of the epididymis. These changes caused softer testicular parenchyma.